2019
DOI: 10.1371/journal.pntd.0007418
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi surface mucins are involved in the attachment to the Triatoma infestans rectal ampoule

Abstract: Background Trypanosoma cruzi , the agent of Chagas disease, is a protozoan parasite transmitted to humans by blood-sucking triatomine vectors. However, and despite its utmost biological and epidemiological relevance, T . cruzi development inside the digestive tract of the insect remains a poorly understood process. Methods/Principle findings Here we showed that Gp35/50 kDa mucins, the major surface gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 86 publications
1
19
0
Order By: Relevance
“…cruzi metacyclics. Our results in combination with published by Camara et al [50] show the great potential of using scFv-10D8 in paratransgenesis approach in a format similar to that used for T . brucei , either alone or in combination with lytic peptides to interfere with parasite::insect interaction.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…cruzi metacyclics. Our results in combination with published by Camara et al [50] show the great potential of using scFv-10D8 in paratransgenesis approach in a format similar to that used for T . brucei , either alone or in combination with lytic peptides to interfere with parasite::insect interaction.…”
Section: Discussionsupporting
confidence: 82%
“…Camara et al [50] have reported that gp35/50 is a key molecule required for parasite attachment to the internal cuticle of the triatomine rectal ampoule, thus affecting epimastigote to metacyclic trypomastigotes differentiation. These author suggest that targeting gp35/50 is appealing mechanism to block parasite transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Sialylation may also reduce the susceptibility of the parasite to anti-α-Gal antibodies present in the mammalian bloodstream (Pereira-Chioccola et al, 2000), allowing colonization and infection. Recently, T. cruzi mucins were also associated with parasite attachment to the internal cuticle of the triatomine rectal ampoule, a critical step leading to T. cruzi differentiation into infective forms to mammalian host cells (Cámara et al, 2019).…”
Section: Mucins Mlms and Diseasesmentioning
confidence: 99%
“… 84 Also, surface mucins of T. cruzi seem to be involved in the attachment, but Gp35/50 kDa mucins cover the whole body of the epimastigotes, not only the small hydrophobic region. 85 …”
Section: Development Of Trypanosoma Cruzi In the Vector – Effects Of The Vectormentioning
confidence: 99%